2017
DOI: 10.1002/eco.1848
|View full text |Cite
|
Sign up to set email alerts
|

How the evaporation of dry dune grasslands evolves during the concerted succession of soil and vegetation

Abstract: Sustainable water and vegetation management of coastal dunes requires fundamental knowledge of how interactions between soil, water, and vegetation evolve during succession. Therefore, we quantified the effect of succession on evaporation in dry dune grasslands of the Netherlands. OnIn general, the vascular plant cover is smaller and the succession speed is slower on equator-facing slopes, which are relatively dry.Mosses and lichens are present as pioneer species or as understory vegetation in coastal dunes. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…In the last 20 yr, the practice has changed, and extensive apricot orchards have been established on former sloped or terraced field. Many studies have focused on variations in soil water in different land cover types in hillslope areas in comparable arid and semiarid regions in the world (Lawrence & Hornberger, 2007;Voortman, Fujita, Bartholomeus, Aggenbach, & Witte, 2017). On the Loess Plateau, soil water circulation and variation have long been an issue of focus (Yang et al, 2014;Zhang & Shangguan, 2018).…”
Section: Core Ideasmentioning
confidence: 99%
“…In the last 20 yr, the practice has changed, and extensive apricot orchards have been established on former sloped or terraced field. Many studies have focused on variations in soil water in different land cover types in hillslope areas in comparable arid and semiarid regions in the world (Lawrence & Hornberger, 2007;Voortman, Fujita, Bartholomeus, Aggenbach, & Witte, 2017). On the Loess Plateau, soil water circulation and variation have long been an issue of focus (Yang et al, 2014;Zhang & Shangguan, 2018).…”
Section: Core Ideasmentioning
confidence: 99%
“…Soil type, depth, water status, fertility, pH, and other factors have important effects on the AM fungal community [46]. In a past study, ectomycorrhizal fungal diversity was higher on sunny aspects than on shady aspects, probably due to differences in the distribution of plants in different aspect orientations caused by differences in insolation, water, and heat conditions [47]. This study found that soil nutrient characteristics were relatively better on NF than on SF.…”
Section: Effects Of Aspects and Other Factors On The Characteristics ...mentioning
confidence: 54%
“…In een zeer beperkt aantal gevallen lijkt extreme droogte ook tot een positieve ontwikkeling te kunnen leiden. De droogte zorgt voor meer openheid in de vegetatie en daarmee voor meer verstuiving, wat gunstig is voor duinen en zandverstuivingen waar verstuiving een probaat middel is tegen atmosferische depositie (Witte et al, 2008;Voortman et al, 2017;Bartholomeus et al, 2012;Witte et al, 2012;Aggenbach et al, 2020).…”
Section: Extreme Droogteunclassified